Dictators, democracy, and American public culture : envisioning the totalitarian enemy, 1920s - 1950s - Alpers, Benjamin Leontief 1965- (Cultural studies of the United States, 2003)
The romance of a dictator : dictatorship in American public culture, 1920s-1935 -- The totalitarian state : modern dictatorship as a new form of government, 1920s-1935 -- The disappearing dictator : declining regard for dictators amid growing fears of dictatorship, 1936-1941 -- The audience itself is the drama : dictatorship and the regimented crowd, 1936-1941 -- Dictator isms and our democracy : the rise of totalitarianism, 1936-1941 -- This is the army : the problem of the military in a democracy, 1941-1945 -- Here is Germany : understanding the Nazi enemy, 1941-1945 -- The battle of Russia : the Russian people, communism, and totalitarianism, 1941-1945 -- A boot stamping on a human face--forever : totalitarianism as nightmare in postwar America